On the variability of tidal fronts on a macrotidal continental shelf, Northern Patagonia, Argentina - Pisoni, Juan Pablo (2015)
Tidal fronts are associated with the transition between homogeneous and vertically stratified water and characterized by the simultaneous availability of light and nutrients that enhance the growth of marine productivity. We study the variability in the position of two tidal fronts located in Patagonia Argentina: the San Matías and Valdés fronts. The rate of tidal dissipation in these regions is among the highest of the world ocean. The study is based on the analysis of over 1200 satellite derived sea surface temperature images. The results indicate that the mean monthly position of both fronts is strongly linked to the characteristics of the bottom topography. In response to increasing surface heat flux the fronts displace toward shallower areas. Similarly, a slight displacement towards deeper waters is observed when the heat flux decreases. High frequency variability is revealed by the standard deviation around monthly averages. At the mouth of San Matías gulf, the front location variability in the spring-neap cycle is around 10 km, while east of Valdés Peninsula the fortnightly cycle is masked by high frequency fluctuations (~30 km) governed by meanders and meso-scale filaments. A simple conceptual model is proposed that suggests that the mean frontal position is determined by the bottom topography while its seasonal variability is driven by the surface heat flux, and the front intensity is modulated by the spring-neap transition.